Alih-Alih Kesadaran Palsu dalam Ujaran Kebencian: Antara Persekusi dan Kriminalisasi - Lucky Nurhadiyanto (Universitas Budi Luhur, 2017)
The acceleration of hate speech cases have increased significantly in recent years. Crime statistics show the cases of hate speech as the highest in 2016 and 2017 based on cyber crime classification. This paper tries to raise the issue involving three cases has become viral. Reactions related to the point of view of false consciousness in the perspective of sociology of law. False consciousness in the law have two ways. First, basis of the dominance of state power. Problems in this short article wants to provide a view of false consciousness relating to persecution and criminalization in hate speech cases. Our discussion will coverage three things. First discussion concerns in the main idea of modern law which related to Western culture. Second discussion relates to the assumption that law will not satisfaction to all parties. Last discussion about the principle of the logic of law which is freedom, equality, and equality based on the ruling social class. For certain communities, law have prejudice to push some parties with the assumption about injustice, inequality, and deliberation. To analyzed this case, the author use seven elements of false consciousness, like instrumental and expressive dimension of social action, the result of undesirable, contradictions and differences between words and action, separation of tools and problem solving, various groups of social relations, communication and relations, and continuity and change. Debate over hate speech leads to a form such as lack of interpretation about formal law between persecution and criminalization. The author try to give some solutions in two ways. The first is to fill the interpretation of ontological and epistemological aspects of legal principle in hate speech, such as freedom, equality and other things that have been generally accepted and applied in society. Meanwhile, second solution is through legal efforts to introspect itself according to the organizational structure to respond social conflicts.